Taste disturbance following tonsillectomy-a prospective study - Heiser, Clemens; Landis, Basile N.; Giger, Roland; Cao Van, Helene; Guinand, Nils; Hörmann, Karl; Stuck, Boris (The laryngoscope, 2010)
Objectives/Hypothesis: Persistent taste disturbance is a rare complication after tonsillectomy and mainly documented by case reports or a few retrospective and prospective trials with a limited number of patients. None could clarify frequency, time course, or prognosis of long-lasting dysgeusia after tonsillectomy. The aim of the study was to provide a symptom-based follow-up after tonsillectomy to assess postoperative taste disorders. Study Design: Prospective clinical trial. Methods: From December 2007 to June 2009 adult patients undergoing tonsillectomy were asked to take part in the trial. Two hundred twenty-three patients (119 female, 104 male; mean age, 33 ± 13 years) were included. The day prior to surgery, and 2 weeks and 6 months after tonsillectomy a standardized questionnaire was completed by patients. The questionnaire focused on taste function, taste disorders, pain, foreign body sensation, and bleeding episodes after tonsillectomy. Results: One hundred eighty-eight (2 weeks) and 181 (6 months) patients returned the questionnaires. Thirty-two percent (n = 60) of patients reported taste disorders after tonsillectomy 2 weeks postoperatively and 15 patients (8%) at 6-month follow-up. Metallic and bitter parageusia were most frequently reported. The mean ratings of gustatory function were significantly lower 2 weeks after surgery (P < .001) and reached preoperative values 6 months after surgery. Almost 30% of patients reported postoperative bleeding, 10% long-lasting postoperative pain, and 20% foreign body sensation. Conclusions: Long-lasting taste disturbance (metallic and bitter parageusia) after tonsillectomy is more frequent than previously reported. Long-lasting pain and foreign body sensation seem to be common symptoms. With regard to these results, a thorough preoperative explanation is mandatory. Laryngoscope, 2010